'Not just theatre, also politics, law': on dramaturgical ethics and collective playwriting in Deportation Centre Sjælsmark. Issue 4 (2nd October 2022) - Grøn, Helene
ABSTRACT: This article reflects on the ethics and process of writing and performing the play This Is Us with a group of rejected asylum seekers from Deportation Centre Sjælsmark in Denmark. Positioned within larger frameworks of political and media hostility, the group pushed for a more radical approach of 'not just theatre', but called instead for solidarity within and beyond moments of collective writing. From this process, 'dramaturgical ethics' arose as an aesthetic and ethical practice, which can support thinking through responsibilities and relationalities involved in research, theatre making and entering into the world together.